2009
DOI: 10.3390/en20200226
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Global Energy and Nutrient Cycles through Application of Biogas Residue to Agricultural Land – Potential Benefits and Drawback

Abstract: Anaerobic digestion is an optimal way to treat organic waste matter, resulting in biogas and residue. Utilization of the residue as a crop fertilizer should enhance crop yield and soil fertility, promoting closure of the global energy and nutrient cycles. Consequently, the requirement for production of inorganic fertilizers will decrease, in turn saving significant amounts of energy, reducing greenhouse gas emissions to the atmosphere, and indirectly leading to global economic benefits. However, application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(148 citation statements)
references
References 95 publications
(113 reference statements)
5
136
0
7
Order By: Relevance
“…An important but little understood aspect of biogas production is its overall impact on soil C and N cycling. Increased biogas production from organic waste will inevitably lead to higher input of its digestate to the soil amendments as fertilizers (Arthurson, 2009). Möller and Stinner (2009) showed that N 2 O-N emissions increase remarkably after shallow injection of slurry in closed slots, particularly if digested slurry was applied.…”
Section: Soil Amendment Of Digestatementioning
confidence: 99%
“…An important but little understood aspect of biogas production is its overall impact on soil C and N cycling. Increased biogas production from organic waste will inevitably lead to higher input of its digestate to the soil amendments as fertilizers (Arthurson, 2009). Möller and Stinner (2009) showed that N 2 O-N emissions increase remarkably after shallow injection of slurry in closed slots, particularly if digested slurry was applied.…”
Section: Soil Amendment Of Digestatementioning
confidence: 99%
“…Field and pot trials to date report positive effects of digestate application to arable land in terms of yields (Stinner et al 2008, Arthurson 2009, Gunnarsson et al 2010 or no significant effects (Ross et al 1989, Bath andElfstrand 2008). Literature on the application of digestates as fertilisers for vegetables is very scarce.…”
mentioning
confidence: 99%
“…Mineralization of macromolecules by anaerobic digestion (Moller and Muller, 2012 which also play a vital role in determining the suitability of a digestate as a fertilizer (Alburquerque et al, 2012). Studies have shown that anaerobic digestates can potentially benefit crop growth as well as nitrogen uptake, although careful monitoring is necessary to ensure a constant soil quality in the early stages (Arthurson, 2009). In this study, a nutrient recycling strategy was tested for the cultivation of Scenedesmus acutus, which has been selected as a candidate for large scale CO 2 mitigation and as a feedstock for anaerobic digestion and biodiesel production due to its high growth rate, hardiness, and oil content Shin et al, 2014;and Wilson et al, 2014).…”
Section: -7012/2016/8(1)/013116/14mentioning
confidence: 99%